Comparison of Casein Phosphopeptide Amorphous Calcium Phosphate Fluoride and Fluoride Varnish on Remineralization of Early Caries Lesions Around Orthodontic Brackets - Vahid Mollabashi; Soussan Irani; Azadeh Kazemisaleh; Sheida Gharagozlou; Maryam Seyedtabib (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: Orthodontic treatment increases the risk of caries and enamel white spot lesions incidence onthe buccal surface of teeth. This study aims to compare the effect of Casein PhosphoPeptide AmorphousCalcium Phosphate Fluoride and fluoride varnish on remineralization of white spot lesions around orthodonticbrackets.Materials and Methods: In this in-vitro study, 60 premolars teeth were etched for 15 seconds. Then bracketswere bonded with Relicane bond. All teeth were immersed in a demineralization solution for 4 days.The lower part of the bracket was painted with nail polish to prevent the effect of a remineralizing agentto serve as a control group. The teeth were divided into 4 groups, Group 1: treated with fluoride varnish for3 weeks (one-time application), Group2: treated with fluoride varnish for 6 weeks (two-time application),Group 3: treated with casein phosphopeptide and amorphous calcium phosphate with fluoride (CPP-ACPF)for 3 weeks (twice a day), Group 4: treated with CPP-ACPF for 6 weeks (twice a day). Remineralizing agentwas applied on the occlusal of bracket for every tooth Area.then the depth of specimens in treatment and control groups was measured by AutoCAD 2007. Pair-T testand repeated measured ANOVA were used for data analysis by SPSS 23.Result: There was no statistically significant difference between each group of treatment. However, meanremineralization depth in group fourth and mean remineralization area in group three were higher than othergroups.Conclusion: Fluoride varnish and CPP-ACPF have the potential to treat the white spot lesion which iscreated during orthodontic treatment. According to less fluoride varnish use, it seems this substance is abetter option in case of patient’s cooperation is not good.